Determination of the Accurate Tooth Length and Apical Constriction Measurements by different Methods in Mandibular Premolar Teeth - Hatem Abdulhaleem, Sameer (International Journal of Psychosocial Rehabilitation, 2020)
During this study, the accurate tooth length and the accurate apical constriction measurement were determined in lower premolar teeth in 43 lower premolar teeth in a sample of Iraqi patients who attended a private dental clinic for root canal treatment in their mandibular premolar teeth. All these teeth were examined by a ZX mini apex locator and digital radiography, and all samples were recorded on the monitor of a MAYRAY (Xpod) sensor imaging system. The electronic working length was determined by the ZX mini apex locator, and the patients were examined by a bisecting angle periodical digital radiographic machine (CSN digital radiographic machine). And the measurements were applied on the monitor of the MYRAY (Xpod) sensor imaging system; then the formula of direct fit was applied to obtain the coefficient factor of shortness and elongation of the radiographic image for each tooth. The distance mean of apical constriction to the apical end of the tooth end (radiographic apex) was found to be 1.26 mm; the largest distance was 1.88 mm, and the smallest distance was 0.69 mm. The mean of the lower premolar teeth length was found to be 20.92 mm with a range of (18.48-23.74) mm. The measurements were carried out with the aid of a ZX mini apex locator and a MYRAY (Xpod) sensor imaging system. It can be concluded that using ZX mini with the MAYRAY imaging system during root canal therapy has accurate determination of working length and the distance between the apical constriction and radiographic apex measurements, in addition to the importance of the combination of the EWLs with the digital imaging system in determination of accurate working length and reduction of unnecessary radiation exposure to the patient.